Development and Validation of an Instrument for Measuring Language Development in 4 to 5 Years Old Children - Ayu, Sovia Mas; Dewi, Asmara; Kuswanto, Cahniyo Wijaya; Mardiana , Mardiana (Golden Age: Jurnal Ilmiah Tumbuh Kembang Anak Usia Dini, 2024)
This research aimed to develop and validate an instrument to measure language development in children aged 4 to 5 years in kindergarten. The study followed the Plomp development model, encompassing five phases: initial investigation, design, realisation, test, evaluation and revision, and implementation. The initial investigation involved analysing theories and existing early childhood language development research. The design phase produced an initial draft of the instrument, which included a language development measurement tool, a validation questionnaire, and a user response questionnaire. Expert validation was conducted using Aiken's formula to establish content validity. The instrument was then tested in three kindergartens with a sample size of 194 children. Confirmatory Factor Analysis (CFA) and descriptive analysis assessed the model’s fit and instrument reliability. Results indicated that the instrument had satisfactory content validity and construct reliability (CR > 0.7), though some fit indices, such as the Comparative Fit Index (CFI), were below ideal thresholds. The validated instrument consists of two language development scales: receptive language (e.g., understanding stories, commands, rules) and expressive language (e.g., asking and answering questions, verbal communication). The study's findings imply significant applications for early childhood education, offering a standardised tool for assessing language development, guiding curriculum design, and enabling targeted interventions to improve language outcomes. Despite its strengths, the study acknowledges limitations, such as the need for better-fit indices and further empirical testing with diverse populations. Future research should focus on longitudinal studies to explore the long-term impacts of the instrument and incorporate technological advancements to enhance its accuracy and relevance. Continuous refinement and validation will ensure the instrument’s effectiveness in measuring early childhood language development.